Effect of glutathione depletion and oral N-acetyl-cysteine treatment on CD4+ and CD8+ cells - Kinscherf, Ralf; Fischbach, Thomas; Mihm, Sabine; Roth, Steffen; Hohenhaus-Sievert, Elke; Weiss, Claus; Edler, Lutz; Bärtsch, Peter; Dröge, Wulf (The FASEB journal, 1994)
HIV-infected individuals and SIV-infected rhesus macaques have, on the average, decreased plasma cysteine and cystine concentrations and decreased intracellular glutathione levels. We show that the cysteine supply and the intracellular glutathione levels have a strong influence on the T cell system, A study of healthy human subjects revealed that persons with intracellular glutathione levels of 20-30 nmol/mg protein had significantly higher numbers of CD4+ T cells than persons with either lower or higher glutathione levels. Persons who moved during a 4-weck observation period from the optimal to the suboptimal range (10-20 nmol/mg) experienced, on the average, a 30% decrease in CD4+ T cell numbers. This decrease was prevented by treatment with N-acetyl-cysteine (NAC). NAC caused this relative increase of CD4+ T cell numbers in spite of decreasing glutathione levels and not by increasing the glutathione level. Our studies suggest that the immune system may be exquisitely sensitive not only against a cysteine and glutathione deficiency but also against an excess of cysteine.—Kinscherf, R., Fischbach, T., Mihm, S., Roth, S., Hohenhaus-Sievert, E., Weiss, C., Edler, L., Bärtsch, P., Dröge, W. Effect of glutathione depletion and oral N-acetyl-cysteine treatment on CD4+ and CD8+ cells. FASEB J. 8: 448-451; 1994.